Análisis para la implementación de políticas y equipamientos para fortalecer las redes inalámbricas de la UTB. - Morejón Mosquera, Tania Stefania (2022)
As the benefits of wireless technology drive organizations to employ their own wireless networks, the issue of security has become increasingly important. Wireless networks pose their own distinctive security challenges for those organizations that adopt the technology. This research is not a review of the various wireless security technology measures; This document is the approach of a wireless security policy contribution whose mission is to strengthen communications through the spectrum, emphasizing the weakness of current wireless security models and establishing a framework for the creation of an effective wireless security policy. for sensitive organizations. For this reason, it is possible to describe the contribution of the research for the Technical University of Babahoyo based on the voice, data and video transmission mechanism with due regulation and faithful compliance with the 802.11 standard in its scope defined by coverage, quality of service, quality of user experience and for the heat and penetration tests carried out in vitalized environments for the infrastructure, distribution system and ad hoc mode; the same ones that are part of the narrow gap between the provision of technology and the implementation of standards that manage wireless connection devices with faithful compliance with the cost-benefit analysis of a standardized network.